Крайові задачі для нелінійних еліптичних рівнянь з параметрами. Застосування методу послідовних наближень - Границя, Ю. А. (ХНУРЕ, 2019)
The given work is devoted to boundary value problems for nonlinear elliptic equations with parameters. The paper presents a mathematical model of the problem in choosing of migration model in population genetics. As a method for solving the problem is applied the method of successive approximation. At the same time, the area in which the problem is considered is such that the Green function is unknown to it. Thus, the initial nonlinear problem is reduced to a sequence of linear boundary value problems. Each of the obtained problems can be solved by the Ritz method or the least squares method.
Keywords: модель міграції популяції; метод послідовних наближень; функція Гріна; метод Рітца